Pengaruh Literasi Keuangan, Presepsi Manfaat dan Kepuasan Pengguna Terhadap Minat penggunaan e-WALLET OVO Pada Mahasiswa S1 Akuntansi Undiksha: Pengaruh Literasi Keuangan, Presepsi Manfaat dan Kepuasan Pengguna Terhadap Minat penggunaan e-WALLET OVO Pada Mahasiswa S1 Akuntansi Undiksha - Yudistira, Kadek; Masdiantini, Putu Riesty (Universitas Pendidikan Ganesha, 2023)
The study aims to find out the impact of financial literacy, perception of benefits, and user satisfaction on the interest in using e-Wallet OVO. This research is a type of quantitative research, where the population in this study is a students of the Bachelor of Accounting Study Program 2018-2020. Sampling techniques are purposive sampling to obtain a sample of as many as 100 students. The type of data used in this study is primary data and the analytical technique used is a double linear regression analysis test. The results of this study show that the variables of financial literacy (X1), benefit perception (X2), and user satisfaction (X3) have a positive and significant influence on the interest in using e-Wallet OVO in Undiksha's Bachelor of Accounting students. This suggests that the better understanding of financial literacy, the better perception of benefits, the higher the user satisfaction rate, then will increase the interest in using e-Wallet OVO.